REALISASI KELUARGA SAKINAH MAWADDAH WARAHMAH BAGI PENYANDANG DISABILITAS DALAM PERSPEKTIF FIQH MUNAKAHAT - Suci Cahaya Ningsi; Agus Muchsin; Saidah Saidah; Islamul Haq; Muhiddin Bakry (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2026)
This study examines marriages of persons with disabilities in realizing sakinah, mawaddah, and rahmah families from the perspective of fiqh munakahat. This research is a field study using a qualitative approach conducted in Panca Rijang District, Sidenreng Rappang Regency. Data were collected through observation, in-depth interviews, and documentation involving three married couples where one partner is a person with physical or sensory disabilities. The results show that efforts to build a sakinah family include mutual understanding of roles and obligations, cooperation in economic and domestic responsibilities, openness, and strengthening faith in Allah SWT. Supporting factors include spousal and family support, while inhibiting factors consist of physical limitations, unstable income, differences of opinion, and challenges in child-rearing. From the perspective of fiqh munakahat, marriages of persons with disabilities remain valid and oriented toward achieving the objectives of marriage (maqashid al-nikah), particularly tranquility, affection, and compassion within the household.